A meta-analysis indicates that the regulation of cell motility is a non-intrinsic function of chemoattractant receptors that is governed independently of directional sensing - José Luis Rodríguez-Fernández; Olga Criado-García (Frontiers in Immunology, 2022)
Chemoattraction, defined as the migration of a cell toward a source of a chemical gradient, is controlled by chemoattractant receptors. Chemoattraction involves two basic activities, namely, directional sensing, a molecular mechanism that detects the direction of a source of chemoattractant, and actin-based motility, which allows the migration of a cell towards it. Current models assume first, that chemoattractant receptors govern both directional sensing and motility (most commonly inducing an increase in the migratory speed of the cells, i.e. chemokinesis), and, second, that the signaling pathways controlling both activities are intertwined. We performed a meta-analysis to reassess these two points. From this study emerge two main findings. First, although many chemoattractant receptors govern directional sensing, there are also receptors that do not regulate cell motility, suggesting that is the ability to control directional sensing, not motility, that best defines a chemoattractant receptor. Second, multiple experimental data suggest that receptor-controlled directional sensing and motility can be controlled independently. We hypothesize that this independence may be based on the existence of separated signalling modules that selectively govern directional sensing and motility in chemotactic cells. Together, the information gathered can be useful to update current models representing the signalling from chemoattractant receptors. The new models may facilitate the development of strategies for a more effective pharmacological modulation of chemoattractant receptor-controlled chemoattraction in health and disease.